Simulation studies of non-toxic tin-based perovskites: Critical insights into solar performance kinetics through comparison with standard lead-based devices. (June 2019) - Ahmed, Saquib; Shaffer, Jon; Harris, Jalen; Pham, Michael; Daniel, Abishai; Chowdhury, Shaestagir; Ali, Aboubakr; Banerjee, Sankha
Abstract: We have simulated the operation and functionality of a working Sn-based perovskite solar cell device using GPVDM and compared it against a Pb-based device. The results are extremely promising in that they showcase comparable cell efficiencies, with the Sn-based device showing a highest 21.3% efficiency (Jsc of 332.8 A/m 2, Voc of 0.839 V, FF of 0.764) compared to 23.4% of its Pb counterpart (Jsc of 349.3 A/m 2, Voc of 0.811 V, FF of 0.828), at similar active layer thicknesses. A deeper study of each of the Jsc, Voc and FF trends provide keen insight into charge transfer kinetics within the device, paving the way to optimal experimental setups for fabricating the most efficient non-toxic perovskite devices. Graphical abstract: Image 1 Highlights: A Sn-based perovskite solar cell is simulated using the GPVDM software and compared against a Pb-based device. Results showcase a similar optimal efficiency value of the Sn-based device (21.3%) compared to the Pb-based one (23.4%). The results delineate and clarify the kinetics that drive the efficiency value differences between simulation and experiment.